TINJAUAN MASLAHAH MURSALAH TERHADAP PENENTUAN PERWALIAN ANAK DILUAR NIKAH (Studi Kasus Kantor Urusan Agama Sidomukti Kota Salatiga) - Jihan Al Layyinah; Asfa Widiyanto; Sukron Ma'mun (Institut Agama Islam Darul Falah Bondowoso, 2026)
This study examines the application of the concept of maslahah mursalah in determining lineage and determining marriage guardians for children born out of wedlock by officials at the Office of Religious Affairs (KUA). This focus is emphasized from the outset to observe how considerations of maslahah are used in Islamic legal practice when cases arise that are not explicitly explained in the texts. The study uses a qualitative, descriptive-empirical approach through observation, interviews, and documentation, and is strengthened by a review of Islamic legal regulations and literature, Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law (KHI). The results show that KUA officials prioritize a careful, dialogical, and maslahah-oriented approach in determining lineage status and determining marriage guardians. These considerations are directed at balancing Islamic legal norms with the practical needs of the community, so that decisions are made in line with positive regulations as well as the values ​​of maqāṣid al-syarī‘ah. The use of maslahah mursalah serves as a basis for ensuring that decisions are beneficial and avoid harm, without the need for lengthy theoretical explanations. This finding shows that the concept of maslahah mursalah remains relevant and applicable in contemporary Islamic legal practice, especially in the KUA environment which deals directly with the social dynamics of society. Keywords: Maslahah Mursalah, KUA, Marriage Guardian, Children Out of Wedlock